Women under patriarchy: an analysis on Lee Su Kim’s manek mischiefs: of patriarchs, playboys, and paramours - Lee, Yong Shan (2021)

(untitled)
Patriarchal oppression changes across time which results in the change in the form of women oppression and subordination as well as the adaptation of resistance by women to combat the established gender injustice. Lee Su Kim’s Manek Mischiefs: Of Patriarchs, Playboys and Paramours is a Malaysian literary work that uncovers the influence of patriarchy heritage on the portrayal of women as subordinates which has refrained them from gaining the courage to establish their sense of identity. Drawing from the postcolonial feminism perspective, Western feminists tend to overlook the oppression faced by women from the Third World, as they neglect the element of ethnicity which can cause further complexities in resisting the oppression. The purpose of this research is to analyse and discuss the portrayal of women characters and the resistance applied to emancipate from the chain of patriarchal oppression in the Peranakan community. I conducted a textual analysis to distinguish the components in four selected short stories and to extensively interpret the presence of patriarchal oppression, portrayal of women and the forms of resistance shown with the support of textual evidence. It is observed that the patriarchy system generated from the participation of the male and female is the main cause of the sustainability of female oppression and subordination in the society. Besides, men who conform to the Chinese patriarchy tend to appear as the victims under its strict cultural practices. I conclude that participation of women in the practice of patriarchal oppression is the impetus of the prolonged patriarchal practices and the gender of male should also be reconceptualised in future Peranakan literary analysis. As modern changes emerge, women uphold a sense of courage in forging their self-identities in order to emancipate from this circle of oppression.